2003
DOI: 10.1021/ma034623j
|View full text |Cite
|
Sign up to set email alerts
|

Crystallization Behavior and Morphology of Biodegradable Polylactide/Layered Silicate Nanocomposite

Abstract: An intercalated polylactide (PLA)/layered silicate nanocomposite was prepared by simple melt extrusion of PLA and organically modified montmorillonite. The detailed crystallization kinetics and morphology of neat PLA before and after nanocomposite preparation were studied by using polarized optical microscopy, light scattering, differential scanning calorimetric, and wide-angle X-ray diffraction analyses. The overall crystallization rate and spherulitic texture of pure PLA were strongly influenced in the prese… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

16
265
2
4

Year Published

2010
2010
2017
2017

Publication Types

Select...
5
4
1

Relationship

0
10

Authors

Journals

citations
Cited by 409 publications
(287 citation statements)
references
References 24 publications
16
265
2
4
Order By: Relevance
“…Among all these polymers, poly(lactic acid) (PLA) is one of the most promising because it is thermoplastic, biocompatible and has a high strength, a high modulus, and good processability [143]. PLA also has been revealed an inefficient crystallization process for both the lower crystallization rate and crystallinity as compared with other polymers [144][145][146][147].…”
Section: Polymeric Bio-related Nanocompositesmentioning
confidence: 99%
“…Among all these polymers, poly(lactic acid) (PLA) is one of the most promising because it is thermoplastic, biocompatible and has a high strength, a high modulus, and good processability [143]. PLA also has been revealed an inefficient crystallization process for both the lower crystallization rate and crystallinity as compared with other polymers [144][145][146][147].…”
Section: Polymeric Bio-related Nanocompositesmentioning
confidence: 99%
“…To determine the crystallinity of the sample, the heats of cold crystallization and pre-melt crystallization were subtracted from heat of melting [22].…”
Section: Differential Scanning Calorimetry (Dsc) Analysismentioning
confidence: 99%
“…Incorporation of nucleating agent provides an efficient way to accelerate the crystallization rate, enhance the X c , and improve the heat resistance of PLLA within a short thermal processing time. Many nucleating agents including carbon fillers, cellulose nanocrystals, talc, crystallites of high-melting-point PLLA (hPLLA), and stereocomplex (SC) crystallites of PLLA and poly(D-lactide) (PDLA) have been employed to enhance the crystallization rate of PLLA [36][37][38][39][40][41][42]. Investigations by Yang et al [35,37] indicated that hPLLA showed the most effective nucleation effect for PLLA when compared to talc and SC crystallites.…”
Section: Introductionmentioning
confidence: 99%